2014
DOI: 10.3997/2214-4609.20141624
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Magnitude and Rate of CO2 Dissolution at Bravo Dome Natural Gas Field

Abstract: The injection of carbon dioxide (CO 2 ) captured at large point sources into deep saline aquifers can significantly reduce anthropogenic CO 2 emissions from fossil fuels. Dissolution of the injected CO 2 into the formation brine is a trapping mechanism that helps to ensure the long-term security of geological CO 2 storage. We use thermochronology to estimate the timing of CO 2 emplacement at Bravo Dome, a large natural CO 2 field at a depth of 700 m in New Mexico. Together with estimates of the total mass loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The brine density increases with aqueous CO 2 concentration and the boundary layer can become unstable and lead to convective overturn within the brine (Weir et al 1995;Ennis-King et al 2005). Convective mass transfer can greatly increase the dissolution rate of the injected buoyant CO 2 vapour and hence contributes to safe long-term storage (Neufeld et al 2010;Sathaye et al 2014). In system (a), the brine can easily move laterally due to the open structure: as CO 2 dissolves in the brine, new brine will be filled into the reservoir, thereby rising the CO 2brine interface and keeping the gas pressure constant; in system (b), no brine can escape from or be filled into the reservoir due to the structural closure so that the interface is fixed and the dissolution of CO 2 will reduce the gas pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The brine density increases with aqueous CO 2 concentration and the boundary layer can become unstable and lead to convective overturn within the brine (Weir et al 1995;Ennis-King et al 2005). Convective mass transfer can greatly increase the dissolution rate of the injected buoyant CO 2 vapour and hence contributes to safe long-term storage (Neufeld et al 2010;Sathaye et al 2014). In system (a), the brine can easily move laterally due to the open structure: as CO 2 dissolves in the brine, new brine will be filled into the reservoir, thereby rising the CO 2brine interface and keeping the gas pressure constant; in system (b), no brine can escape from or be filled into the reservoir due to the structural closure so that the interface is fixed and the dissolution of CO 2 will reduce the gas pressure.…”
Section: Introductionmentioning
confidence: 99%
“…However recently, CO 2 trapping at Bravo Dome (New Mexico) -perhaps the largest known natural trap of CO 2 -was analyzed (Sathaye et al, 2014;Gilfillan et al, 2009) and we can compare it here to our previous computations. Like our estimates, most of the CO 2 gas is sequestered at Bravo Dome as dissolved molecular CO 2 present at a pH between 6 and 7, with a moderate amount of aqueous HCO 3 À .…”
Section: Introductionmentioning
confidence: 78%
“…For example, new calculations for the Bravo Dome natural CO 2 gas reservoir are consistent with a large CO 2 plume existing for up to 1.2 Ma (Sathaye et al, 2014). If similar geological place will be chosen for CO 2 sequestration the presence of wellbores can facilitate the CO 2 leakage (Jordan et al, 2015).…”
Section: Reactive Transport Modelingmentioning
confidence: 96%
“…Small-scale experiments and simulations 2,3 have shown that CO 2 dissolved in brine can increase convective forces in the brine and create convective mixing but it has not been proven to occur in large-scale systems such as the Bravo Dome CO 2 deposit. 4 Carbon dioxide dissolved in residual oil is also stored permanently unless, thanks to newer technologies, those resources are produced in the future. Mineral trapping is the safest mechanism to trap CO 2 for long time periods but this mechanism typically takes effect later, after the abandonment of the site (hundreds of years).…”
Section: Introductionmentioning
confidence: 99%